Listeria monocytogenes varies among strains to maintain intracellular pH homeostasis under stresses by different acids as analyzed by a high-throughput microplate-based fluorometry - Cheng, Changyong; Yang, Yongchun; Dong, Zhimei; Wang, Xiaowen; Fang, Chun; Yang, Menghua; Sun, Jing; Xiao, Liya; Fang, Weihuan; Song, Houhui (Frontiers in Microbiology, 2015)
Listeria monocytogenes, a food-borne pathogen, has the capacity to maintain intracellular pH (pHi) homeostasis in acidic environments, but the underlying mechanisms remain elusive. Here, we report a simple microplate-based fluorescent method to determine pHi of listerial cells that were prelabeled with the fluorescent dye carboxyfluorescein diacetate N-succinimidyl ester and subjected to acid stress. We found that L. monocytogenes responds differently among strains toward organic and inorganic acids to maintain pHi homeostasis. The capacity of L. monocytogenes to maintain pHi at extracellular pH 4.5 (pHex) was compromised in the presence of acetic acid and lactic acid, but not by hydrochloric acid and citric acid. Organic acids exhibited more inhibitory effects than hydrochloric acid at certain pH conditions. Furthermore, the virulent stains L. monocytogenes EGDe, 850658 and 10403S was more resistant to acidic stress than the avirulent M7 which showed a defect in maintaining pHi homeostasis. Deletion of sigB, a stress-responsive alternative sigma factor from 10403S, markedly altered intracellular pHi homeostasis, and showed a significant growth and survival defect under acidic conditions. Thus, this work provides new insights into bacterial survival mechanism to acidic stresses.